1992
DOI: 10.1113/jphysiol.1992.sp019110
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C‐mediated enhancement of NMDA currents by metabotropic glutamate receptors in Xenopus oocytes.

Abstract: SUMMARY1. N-Methyl-D-aspartate (NMDA) receptors were expressed in Xenopus oocytes injected with rat brain RNA. The modulation of NMDA-induced currents was examined by activating protein kinase C (PKC) either directly (using phorbol esters) or indirectly (via metabotropic glutamate agonists).2. Bath application of the PKC activator, 4-,f-phorbol-12,13-dibutyrate (PDBu) resulted in a two-fold increase in the NMDA-evoked current at all holding potentials examined (-80 to 0 mV). The inactive (a) stereoisomer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
126
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(132 citation statements)
references
References 50 publications
4
126
2
Order By: Relevance
“…Consistent with this hypothesis, mGluR5 knockout (KO) mice are deficient in NMDA receptor-dependent LTP and spatial learning (Lu et al, 1997;Jia et al, 1998). These effects may be mediated by PKC-mediated potentiation of NMDA receptor function by group I mGluRs (Kelso et al, 1992;Aniksztejn et al, 1991;Skeberdis et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, mGluR5 knockout (KO) mice are deficient in NMDA receptor-dependent LTP and spatial learning (Lu et al, 1997;Jia et al, 1998). These effects may be mediated by PKC-mediated potentiation of NMDA receptor function by group I mGluRs (Kelso et al, 1992;Aniksztejn et al, 1991;Skeberdis et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Of the many Ca*'-mediated processes that might be responsible for the enhanced ethanol sensitivity, we focused on the role of PKC based on the existence of PKC consensus sites among the GluRs (Keinanen et al, 1990) and PKC-dependent receptor phosphorylation (McGlade-McCulloh et al, 1993) together with our work showing that activation of PKC inhibited kainate-induced currents in oocytes expressing different GluR subunits . However, there are reports that failed to show modulation of AMPA/kainate receptors by PKC (Sigel and Baur, 1988;Chen and Huang, 1992;Kelso et al, 1992), indicating that PKC modulation may not be a common mechanism for all of the GluRs or that the conditions required for PKC-dependent phosphorylation may be slightly different for different GluRs. We found that the PKC inhibitor peptide or the PKC inhibitor calphostin C prevented the enhanced ethanol inhibition in high-Ca'+ buffer but had no effect in normal buffer.…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, NMDA potentiates lS,3R-ACPD-stimulated Ins(1,4,5)P3 accumulation, probably by increasing intracellular Ca2" concentration and facilitation of agonist-stimulated PI-PLC activity. These observations suggest that as well as NMDA-receptor/ion channel activity being affected by metabotropic receptor activation (Bleakman et al, 1992;Courtney & Nicholls, 1992;Chen & Huang, 1992;Kelso et al, 1992;Harvey & Collingridge, 1993), reciprocal modulations can also occur, providing additional evidence for the complexities of ionotropic/ metabotropic 'cross-talk' between glutamate receptors which are considered to underlie phenomena such as synaptic plasticity (Madison et al, 1991;Bashir et al, 1993;Behnisch & Reymann, 1993;Bliss & Collingridge, 1993). In contrast, exposure of neonatal cerebral cortex slices to higher concentrations of NMDA causes a rapidly developing inhibition of agonist-stimulated phosphoinositide responses which are most likely to be due to an acute, Ca2"-dependent neurotoxic action of NMDA in this brain preparation.…”
Section: Discussionmentioning
confidence: 99%